IMPROVING PROFIT USING CONTRIBUTION METRICS TO BOOST THE BOTTOM LINE - Cleland, Keith N. (Apress : Imprint: Apress, 2013)
Business of all sizes have a problem: How do you knowỚ in real timeỚ whether you are earning the profit you need to grow or even just stay in business? And which products or services are doing the ỚSheavy liftingỚ<U+00fd> in contributing to profit? Financial statements tell only part of the story. They are backward looking, for one thing, and they generally show results only in the aggregate. Worse, they never seem to reflect the hard work youỚ"re doing on a daily basis. As one manager said, ỚSIf IỚ"m adding 25% profit to every job, why am I getting barely 5% net profit at the end of the year?Ớ<U+00fd> Improving Profit: Using Contribution Metrics℗ to Boost the Bottom Line solves this dilemma. As this book shows, Contribution-Based Activity (CBA) measures focus on two key levers that are fundamental to the operation of any business: financial contribution and units of activity. Knowing how to use these levers gets your company off the treadmill and on your way to stellar profitability. And as the 21 case studies show, CBA is surprisingly easy to apply to businesses of all types and all sizes. What is ỚSfinancial contributionỚ<U+00fd>? Simply the amount above and beyond the cost of goods or materials sold that contributes to covering overhead and creating profit. As entrepreneur, business consultant, and professor Keith Cleland shows, few managers actually know the financial contribution their products and services make, nor how to amplify that contribution by ℗ incremental adjustments to one or both levers. As youỚ"ll learn, the financial tool Cleland created, TARI (Target Average Rate Index), provides insight into each productỚ"s value. YouỚ"ll not only learn which products are contributing the most to the bottom line, but how to unlock the profit potential in run-of-the-mill products or services. Improving Profit will help you: Restore and boost profit levels for your entire operation Relate your daily efforts to℗ a transaction's℗ actual profitability Focus on the two key performance indicators that can help you identify and solve problems affecting finance and productivity Help everyone in the companyỚ from CEO to janitorỚ understand how their activities help or hinder the companyỚ"s fortunes Make effective financial decisions If youỚ"ve ever wondered why your results donỚ"t match your hard work, hopes, and dreams, read this book. As the case studies make clear, identifying and applying TARI results in a significantỚ and often dramaticỚ boost to the bottom-line.℗ ℗ .